Nursing accounting competencies related to HIV in a Papua New Guinea context - Brown, Alistair (Elsevier, 2013)
Nursing administration is an important part of the campaign to eliminate HIV across Papua New Guinea (PNG). This paper considers the critical importance of developing nursing leadership in effective accounting competencies in relation to HIV projects in PNG. The results of the study's textual analysis of audit reports of the Auditor General of PNG revealed a failure on the part of PNG's main health agencies involved with its national HIV program to provide competent financial reporting. In light of these results, this study shows how improving accounting and other financial competencies among nursing leaders would benefit the implementation of the PNG HIV national strategy. The findings of this study have implications not only for the internal control of HIV nursing competencies but also for nursing leadership related to HIV issues in a developing-country context.